DIAGNOSTIC CHALLENGES OF HENOCH-SCHÖNLEIN PURPURA IN PEDIATRIC PATIENTS: UNVEILING THE OVERLAP WITH ACUTE APPENDICITIS : CASE REPORT - Eric, Andreas; Putu Siska, Suryaningsih; Kadek, Suarca; AA Gede Agung Budhi, Kusuma (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
This article highlights the diagnostic complexity of Henoch-Schönlein Purpura (HSP) in pediatric patients, particularly when abdominal pain mimicking acute appendicitis. The objective is to emphasize the importance of comprehensive clinical evaluation to prevent misdiagnosis. Case: A 5-year-old boy with abdominal pain, nausea, and joint pain. Two days before symptom onset, he developed palpable purpura. He was diagnosed with appendicitis and underwent an appendectomy, which confirmed an inflamed appendix. Postoperatively, dermatological consultation diagnosed HSP. The patient received intravenous methylprednisolone and topical therapies, leading to symptom resolution. HSP commonly affects children and can present with gastrointestinal symptoms that mimic appendicitis. A thorough examination must be conducted to ensure that there are no other causes of abdominal pain. Conclusion: Henoch-Schönlein purpura (HSP) and appendicitis can occur simultaneously, although this is rare. A comprehensive evaluation is essential to confirm a diagnosis.